Development Strategy of Microtakaful Institutions: Case Study Working Group Indonesia - Aam Slamet Rusydiana; Abrista Devi (Faculty of Economic and Business, 2017)
Indonesia is becoming one of potential countries in microtakaful institutions development. One of the expert in microtakaful is Takmin Working Group. TWG is a group of initiators who have commitment to develop micro takaful in Indonesia. Its members consist ofexperts in Islamic insurance, micro finance and accounting. The research objectives of this study are to identify and analyze the problems faced by TWG in developing of microtakaful institutions and identify the solutions to solve those kinds of problems, by using AnalticHierarchy Process (AHP) method. The finding of this study shows the most priority solutions that can be undertake by Takmin Working Group to solve these both internal and external problem is information system development, and then followed by innovative product development. Communication & visitation to Islamic micro finance institutions and socialization about micro takaful product to society are being less priority on this matter.DOI: 10.15408/etk.v16i2.5267